Mobility as a Service (MaaS) and Transportation Integration in Jabodetabek: A Thematic Analysis of Infrastructure, User, and Regulatory Perspectives Toward Sustainable Urban Mobility - Dody Suhermawan (Journal of Managerial Sciences and Studies, 2026)
Rapid population growth and increasing mobility in Jakarta and the greater Jabodetabek region have intensified the need for an integrated, multimodal transportation system that supports urban efficiency and sustainability. This study examines the development and implementation of Mobility as a Service (MaaS) as a technology-driven framework that integrates transportation modes, digital platforms, and network management systems to improve passenger mobility. Using a qualitative approach with thematic analysis and data triangulation, data were collected through desk research, in-depth interviews, focus group discussions (FGDs) with academics, practitioners, operators, and government stakeholders, as well as field observation across the 2021–2023 period. The analysis focuses on three main dimensions: infrastructure integration (information technology systems, transportation modes, and regulation), actors and consumers (user types, travel behavior, and communication channels), and value proposition (service integration, modal connectivity, and coverage). The findings reveal that although physical, payment, and schedule integration efforts—such as JakLingko and integrated transit hubs—have progressed, significant challenges remain, including limited first-mile–last-mile connectivity, fragmented fleet management systems, inconsistent regulatory frameworks, and unresolved land and subsidy allocation issues. The study highlights the critical role of integrators and Public-Private Partnerships (PPP) in bridging these gaps, and demonstrates how the combination of MaaS, the Internet of Things (IoT), and Network Management Systems (NMS) can enhance socio-economic welfare, reduce congestion, and support sustainable urban transportation. These findings contribute to a more comprehensive understanding of MaaS implementation in a rapidly urbanizing metropolitan context and offer policy-relevant insights for transportation authorities and service integrators.